The Influence Of Behaviour Centred Design Approaches On The Flame-Based Cookstove-Related Health And Wellbeing Of Indigent South African Households - Maré, Marcel; M’rithaa, Mugendi K. (Machakos University Press, 2021)
The adoption of energy-efficient, clean and safe cookstoves can significantly enhance the health and quality of life of poverty-stricken sub-Saharan households, reducing mortality and poverty and positively impacting the protection of biodiversity and the climate identified in the United Nations Sustainable Development Goals (SDGs). The harmful emissions from inefficient flame-based cookstoves are the leading global cause of disease and death, after only inadequate water, poor sanitation and malnutrition. Multiple stakeholders are implementing programmes to promote access to improved stoves and clean fuels, with the Global Alliance for Clean Cookstoves (GACC) being prominent in dissemination efforts. However, few interventions have borne fruit on a significant scale over time, despite ample support in finding workable solutions. A sustainable transformation in household cookstove-related practices across diverse conditions requires innovative transdisciplinary approaches. The behavioural sciences suggest possible approaches for addressing the complex, interrelated, social, economic and environmental challenges facing communities in sub-Saharan Africa (SSA). Behaviour-focussed design interventions exhibit the possibility of transcending disciplinary boundaries. This paper explores the ability of a Behaviour Centred Design (BCD) approach to change cookstove-related behavioural motivations in a South African context. A series of motivational touchpoints are developed and tested in two representative South African sample areas on a pilot scale. The preliminary results suggest that a BCD approach targeting a set of mapped touchpoints can significantly change the pertinent behavioural motivations related to flame-based cookstoves, responding to a vital evidence gap in efforts to shift inefficient cookstove-related behaviour in a South African low-income context.
Keywords: Behavioural Sciences; Behaviour Centred Design; Improved Cookstoves; UN Sustainable Development Goals